PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN LINGKUNGAN KERJA TERHADAP LOYALITAS KARYAWAN (Studi Kasus Pada Rumah Sakit Syafira Pekanbaru) - Eduwin Kurniawan Siagian; Okta Karneli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aims to determine the effect of transformational leadership style and work environment to employee loyalty at Syafira hospital Pekanbaru. Where the proposed two independent variables and the dependent variable, namely transformational leadership and work environment act as independent variables and loyalty plays as the dependent variable. This study took a number of respondents as many as 82 people and the population in this study is the employees on hospital syafirapekanbaru. In this study, the data was obtained using a questionnaire with a scale of measurement using a Likert scale further processed and analyzed using the validity, reliabelitas, statistical analysis such as linear analysis, t test and f test using SPSS. Results of analysis using multiple linear regression, t test and f test so that it can be seen that the variable transformational leadership of a negative effect on work employee loyalty (H1), that work environment have a significant effect on the employee loyalty (H2), and the significant influence of transformational leadership andwork environment to employee loyalty(H3). Keywords: transformational leadership, work environment, employee loyalty.